Adherence to and Acceptance of Once-Daily Tacrolimus After Kidney and Liver Transplant: Results From OSIRIS, a French Observational Study. Issue 10 (October 2016) - Cassuto, Elisabeth; Pageaux, Georges P.; Cantarovich, Diego; Rostaing, Lionel; Loupy, Alexandre; Roche, Bruno; Duvoux, Christophe; Moreau, Karine; Thervet, Eric; Mazouz, Hakim; Bourhis, Yann; Dharancy, Sébastien; et al.
Abstract : Background: Adherence to immunosuppressive treatments is a major concern in transplanted patients. Methods: This 6-month French observational, longitudinal, prospective study aimed to assess patient adherence to and acceptance of once-daily tacrolimus (Advagraf) initiation in kidney and liver transplant recipients. Data from 1106 patients initiating once-daily tacrolimus during posttransplant follow-up were analyzed. Adherence and acceptance were assessed using self-administered questionnaires at inclusion and at 3 and 6 months. Results: Mean age was 52.4 ± 13.2 years, 61.5% were men. For 94.9% of patients, once-daily tacrolimus was prescribed after switching from twice-daily tacrolimus. At inclusion, 20.9% of patients reported good treatment adherence, 72.0% minor nonadherence, and 7.1% were nonadherent. Mean general acceptance score (range, 0-100) was 77.7 (±24.7). At 3 months, adherence was improved in 21.1%, unchanged in 69.2%, and worsened in 9.7% of patients. Mean general acceptance score was 75.4 (±26.5). General acceptance score was improved in 28.0%, unchanged in 39.4%, and worsened in 32.7% of patients. At 6 months, similar changes in adherence and acceptance were observed. Higher general acceptance score at month 3 was significantly associated with better adherence at month 6. Conclusions: Conversion to once-daily tacrolimus led to an improved rate of adherence at month 3 in more than 20% of patients and a worsened rate of adherence in less than 10% of patients. Abstract : A French observational, longitudinal, prospective study assesses patient adherence of once-daily tacrolimus in kidney and liver transplant recipients. Conversion to once-daily tacrolimus improves adherence rate more than 20% of patients and worsens in less than 10% of patients.